2020
DOI: 10.1016/j.heliyon.2020.e04770
|View full text |Cite
|
Sign up to set email alerts
|

Holistic approach to microwave-reflux extraction and thermo-analytical fingerprints of under-utilized Artocarpus heterophyllus seed wastes

Abstract: The increase in wastes generated from jackfruit seeds has been largely under-utilized in Malaysia. Due to the high nutritional and medicinal content embedded in the cellulosic structure of jackfruit wastes, a need then arises for their physicochemical elucidations. In this study, the extraction of Artocarpus heterophyllus seed was carefully investigated using Taguchi orthogonal optimization design. Complete functional group characteristics and chemical profile of the A. heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…All the extraction methods used in this study had better yields when using ethanol as a solvent; additionally, ethanol extracts had better antioxidant capacity [20]. More recently, Olalere et al [41] used microwaves-assisted extraction (MAE) in jackfruit seeds (5 min of irradiation, 450 W, and 50 • C) and concluded that MAE produces high-quality extracts with a remarkable impact on properties like texture, phenolic exudation, and lower degradation of thermolabile compounds.…”
Section: Emerging Technologiesmentioning
confidence: 73%
See 1 more Smart Citation
“…All the extraction methods used in this study had better yields when using ethanol as a solvent; additionally, ethanol extracts had better antioxidant capacity [20]. More recently, Olalere et al [41] used microwaves-assisted extraction (MAE) in jackfruit seeds (5 min of irradiation, 450 W, and 50 • C) and concluded that MAE produces high-quality extracts with a remarkable impact on properties like texture, phenolic exudation, and lower degradation of thermolabile compounds.…”
Section: Emerging Technologiesmentioning
confidence: 73%
“…Phenolic compounds yield: 17.34 mg/g% [41] Supercritical fluid extraction with CO 2 7.00 g of sample is placed into a column (127.5 mm length × 10 mm diameter and internal volume of 10 cm 3 ) to form the bed of fixed particles. Conditions: temperature of 50 • C, pressure of 12 MPa, CO 2 flow rate of 4.0 mL min −1 , and extraction time of 150 min.…”
Section: Emerging Technologiesmentioning
confidence: 99%